Medicaid expansion and access to naloxone in metropolitan and nonmetropolitan areas. Issue 2 (5th November 2022) - Cheng, Yue; Freeman, Patricia R.; Slade, Emily; Sohn, Minji; Talbert, Jeffery C.; Delcher, Chris
Abstract: Purpose: The opioid crisis remains a major public health concern in the United States. Naloxone is used to reverse opioid overdoses. This study examined Medicaid expansion on naloxone prescriptions in retail pharmacies in metropolitan (metro) and nonmetropolitan (nonmetro) areas (2011‐2017). Methods: We used population average models to evaluate the association of Medicaid expansion at the state level on the number of naloxone prescriptions dispensed and the percentage paid by Medicaid, including adjustment for opioid‐related and state‐level policy covariates. Difference‐in‐difference modeling was performed as a sensitivity analysis. Findings: States that expanded Medicaid had higher unadjusted naloxone dispensing rates and Medicaid‐paid percentage of naloxone in metro and nonmetro areas. Medicaid expansion was not associated with the number of naloxone dispensed in either metro (adjusted rate ratio (ARR) = 1.26, 95% CI: [0.80, 1.97]) or nonmetro (ARR = 0.67, 95% CI: [0.37, 1.19]) areas after covariate adjustment. In metro areas, Medicaid expansion was associated with a significant increase of 3.86 percentage points (95% CI: [0.09, 7.63]) in the Medicaid‐paid percentage of naloxone dispensing compared to nonexpansion states, but this association was not significant in nonmetro areas. There was also a significant time by Medicaid expansion interaction on the Medicaid‐paid percentage of naloxone dispensed (metro: estimate = 0.74, 95% CI: [0.36, 1.12]; nonmetro: estimate = 0.68, 95% CI: [0.17, 1.18]). Conclusions: Medicaid expansion increased naloxone access by increasing the Medicaid‐paid percentage of naloxone prescriptions in metro areas. States with Medicaid expansion had a faster rate of increase in the Medicaid‐paid percentage of naloxone than states without Medicaid expansion in nonmetro areas.